2019
DOI: 10.1038/s41401-019-0320-y
|View full text |Cite
|
Sign up to set email alerts
|

Zinc protects against cadmium-induced toxicity in neonatal murine engineered cardiac tissues via metallothionein-dependent and independent mechanisms

Abstract: Cadmium (Cd) is a nonessential heavy metal and a prevalent environmental toxin that has been shown to induce significant cardiomyocyte apoptosis in neonatal murine engineered cardiac tissues (ECTs). In contrast, zinc (Zn) is a potent metallothionein (MT) inducer, which plays an important role in protection against Cd toxicity. In this study, we investigated the protective effects of Zn against Cd toxicity in ECTs and explore the underlying mechanisms. ECTs were constructed from neonatal ventricular cells of wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 67 publications
1
8
0
1
Order By: Relevance
“…We used Pierce Lactate dehydrogenase (LDH) Cytotoxicity Assay Kit (Thermo Fisher Scientific) to determine the LDH release into the culture medium as previously described 12 . Briefly, 50 µL of each sample medium was transferred to a 96‐well flat‐bottom plate in duplicate wells, mixed with 50 µL of the reaction mixture, then incubated at room temperature for 30 minutes in the dark, followed by the addition of 50 µL of Stop Solution to each sample well.…”
Section: Methodsmentioning
confidence: 99%
“…We used Pierce Lactate dehydrogenase (LDH) Cytotoxicity Assay Kit (Thermo Fisher Scientific) to determine the LDH release into the culture medium as previously described 12 . Briefly, 50 µL of each sample medium was transferred to a 96‐well flat‐bottom plate in duplicate wells, mixed with 50 µL of the reaction mixture, then incubated at room temperature for 30 minutes in the dark, followed by the addition of 50 µL of Stop Solution to each sample well.…”
Section: Methodsmentioning
confidence: 99%
“…In animals, chelators can reduce acute Cd-induced mortality, provided treatment started very soon after Cd ingestion. Zn may exert protective effects against acute Cd toxicity that are partially MT-mediated, as suggested from neonatal murine-engineered cardiac tissues ( Yu et al, 2020 ).…”
Section: Therapymentioning
confidence: 99%
“…The capacity of a biological system to detoxify these reactive intermediates determines how much oxidative stress is experienced by cells on an ongoing basis [ 28 ]. Early in the reaction to oxidative stress, NF-E2-related nuclear factor 2 (Nrf2) is quickly elevated, and as a protective strategy, it then translocates to the nucleus to boost the transcription of oxidative stress response genes [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that Zn-induced metallothionein overexpression contributes to the Zn protective effect [ 29 , 31 ]. In the present investigation, we discovered that Zn might, in a dose-dependent manner, cause MT overexpression.…”
Section: Discussionmentioning
confidence: 99%